Introduction to the special section: Teaching critical GIS | Teaching GIS critically. - Warren, Stacy (Canadian Geographer)
Even more contentious is the question of what teaching critical GIS entails, echoing questions raised by Elwood and Wilson (2017) who observe that teaching critical GIS and teaching GIS critically are not necessarily the same thing. Together, they represent a candid and realistic examination of how the contours of the medium, be it open source GIS, programming code, or artistic materials, can be leveraged to create critical GIS curricular experience that remains relevant to the challenges around us. Recognizing that these far broader changes have impacted how we teach, how students learn, and what it means to interact with GIS software, we set out to contextualize Anna's words in a reflective manner that situates her experiences in longer GIS trajectories. The innovative critical GIS master's program that Anna helped shape back in 2015, for example, experienced the slow-burning financial squeeze described in our paper that necessitated subsequent waves of nimble dodging and trimming.